Pneumoscrotum after colorectal surgery: A case report. Issue 8 (17th June 2018) - Willburger, Johanna; Suter, Basil; Wimmer, Matthias; Kirchhoff, Philipp
Key Clinical Message: Pneumoscrotum is a very rare complication. Currently, very little evidence‐based medicine exists on treatment guidelines. We think a prophylactic antibiotic course and a 48 hours in hospital observation are justified in these rare cases. Abstract : Pneumoscrotum is a very rare complication. Currently, very little evidence‐based medicine exists on treatment guidelines. We think a prophylactic antibiotic course and a 48 hours in hospital observation are justified in these rare cases.